PENDAMPINGAN PENINGKATAN KUALITAS BATU BATA DENGAN LIMBAH SEKAM PADI DAN FLY ASH DALAM PEMBUATAN BATA MERAH DI DESA GAMBIREJO TANJUNGANOM NGANJUK - Agata Iwan Candra; Fajar Romadhon; Faiz Muhammad Azhari (LPPM Universitas Trunojoyo Madura, 2022)
In the construction industry, one of the materials that are often used is brick. Bricks are very much needed including as a wall barrier in residential buildings with non-structural functions. The need for the willingness of bricks according to standards and affordable prices is also increasing, which makes brick production very desirable, especially construction actors. But the use of clay as the only material of brick production will provide the results of bricks that are easily cracked. This causes an increasing scarcity of the main material of clay, even more expensive. Therefore, it is necessary to utilize environmentally friendly waste materials to be the right choice in making innovations, one of which is the use of rice husk waste. The methods used are socialization related to the purpose of community service, extension and transfer of materials technology science, training and assistance in brick production, monitoring and evaluation. The location of the activity was carried out in Gambirejo Village, Tanjunganom Subdistrict, Nganjuk Regency which is a village famous for its red brick industry in Nganjuk Regency. This mentoring activity is in the form of training and extension to improve the knowledge and skills of partners so that the production of the resulting bricks becomes more quality with more efficient production costs.